EVALUASI ATAS PERANAN TEKNOLOGI INFORMASI PADA PROSES AKUNTANSI UNTUK MENGHASILKAN LAPORAN KEUANGAN YANG RELEVAN DAN RELIABLE (Studi Kasus Pada PT Seneca Indonesia) - Elizabeth Tiur Manurung; Tantya Adrianti (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
Today, information technology is developed so rapidly and provides a lot of convenience for the business. With the advances in information technology, corporate accounting process changes from a manual system to computer-based information systems. The use of information technology can also improve internal controls by adding new control procedures are done by a computer, called IT controls. IT controls can help to control the processing of computer-based accounting to produce relevant and reliable financial statements. Therefore, the problem to be studied in this study are: to evaluate the role of information technology in PT Seneca Indonesia’s accounting process and to examine whether the role of information technology in PT Seneca Indonesia has been effective to produce relevant and reliable financial statements. The results showed that the role of information technology in PT Seneca Indonesia’s accounting process has been effective in supporting the production of relevant and reliable financial statements. It is also supported by IT controls that have been implemented by the company sufficiently. The author tries to give some advice to the information technology control weaknesses that was found in this study, such as by implementing segregation of duties in the IT division and implementing cancellation of document.Keywords: information technology, accounting process, IT controls, financial statements, relevant, reliable